(untitled) (Journal of Enam Medical College, 2021)
Childhood granulomatosis with polyangiitis (cGPA), is a rare, potentially fatal necrotizing vasculitis and its clinical features overlap with infection. Clinical manifestations of cGPA varies widely from involvement of upper and/or lower respiratory tract, necrotizing glomerulonephritis and less commonly skin, central nervous system, heart, salivary gland, eye and orbit. A ten-yearold girl was admitted having chronic sinusitis and fever for three months followed by perforating palate ulcer, persistent middle ear effusion, epistaxis, nasal deformity, rapidly progressing pneumonia and necrotizing skin lesions in limbs. Investigations demonstrated high titer of cANCA and vascular granulomatous lesions that confirmed the diagnosis of cGPA. Diagnosis of cGPA at the early stage is difficult because of the nonspecific symptoms which mimic other disorders. This case highlights the difficulty in diagnosing cGPA and the potentially life-threatening consequences of failing to do so. J Enam Med Col 2021; 11(2): 128-132